(untitled) (Boletín Semillero de Investigación en Familia, 2024)
Introduction: informal care through the times, has been assumed by the family or friends of the subject of care, who provide support and assistance to people facing chronic diseases, disabilities, injuries or other health conditions that make them vulnerable and dependent, this care, usually generates fatigue in the caregiver as it does not allow him to take charge of their own daily activities, so it has been generated today various technological tools that allow the organization and timely management of care. Objective: to present technology as a resource to support the work of caregivers, taking advantage of various technological tools. Materials and methods: bibliographic material related to the use of information and communication technology to provide care was consulted in Elsevier, Taylor y Francis, Springer Link. Results: there is little specific literature on the subject. Conclusions: there are different technological tools that favor caregiving and minimize the caregiver’s burden, avoiding risks and worries that may lead not only to complications in the caregiver, but also to future problems in the informal caregiver.